2007
DOI: 10.1002/cncr.22675
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variation in return to baseline values of patient‐reported outcomes in older prostate cancer patients

Abstract: BACKGROUND.Ethnic variation in patient‐reported outcomes such as health‐related quality of life (HRQoL) and satisfaction with care are understudied areas in the management of elderly prostate cancer (PCa) patients.METHODS.In this prospective cohort study, between the years 2002 and 2004, the authors recruited 214 older (≥65 years) men with newly diagnosed PCa from an urban academic hospital and a Veterans Administration hospital. Participants completed generic (SF‐36), prostate‐specific (UCLA‐PCI) HRQoL, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 39 publications
2
46
0
Order By: Relevance
“…Moreover, clinical studies revealed ethnic background as a crucial determinant in analgesic requirements in several pain states such as post-operative [15], chronic [45,46] and cancer pain [47,48]. On the other hand, the duration of opioids analgesia is different among patients with different ethnic backgrounds [49].…”
Section: The A118g Distribution Across Human Populationsmentioning
confidence: 99%
“…Moreover, clinical studies revealed ethnic background as a crucial determinant in analgesic requirements in several pain states such as post-operative [15], chronic [45,46] and cancer pain [47,48]. On the other hand, the duration of opioids analgesia is different among patients with different ethnic backgrounds [49].…”
Section: The A118g Distribution Across Human Populationsmentioning
confidence: 99%
“…Jayadevappa et al [32] conducted a prospective study evaluating QOL and satisfaction with care after RP or RT. Compared with white patients, black patients were less likely to choose RP as primary treatment, although when statistically controlled, ethnicity was not associated with treatment type in statistical significance.…”
Section: Hrqol In Minority Populationsmentioning
confidence: 99%
“…Furthermore, alterations in HRQoL have been found to persist even many years after PCa treatment (Sanda et al, 2008;Litwin et al, 2001). Alterations in HRQoL in PCa survivors are not completely dependent on choosing treatments: studies have shown that HRQoL is also associated with stage of cancer at diagnosis, socioeconomic, physical and psychological status, comorbidities, HRQoL prior to diagnosis and health care utilization behaviors (Penedo et al, 2006;Jayadeyappa et al, 2007;Lubeck et al, 2001;Litwin et al, 2001;Ramsey et al, 2007;Penson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As with morbidity, there is also a disparity in HRQoL between AA and CA survivors (Penedo et al, 2006;Sanda et al, 2008;Litwin et al, 1999;Jayadeyappa et al, 2007;Lubeck et al, 2001;Johnson et al, 2004;Freedland and Isaacs, 2005;Jenkins et al, 2004;Eton et al, 2001). Though variance in PCa treatment is thought to play a role in this disparity, it has been postulated that AA PCa survivors have lower HRQoL measurements due to lower pretreatment HRQoL, less advantageous sociodemographic characteristics, higher rate of comorbidities, later stage of disease at diagnosis and more issues regarding health care (Penedo et al, 2006;Jayadeyappa et al, 2007;Lubeck et al, 2001;Litwin et al, 2000Ramsey et al, 2007Penson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation